Controlled Activity of the Salmonella Invasion-Associated Injectisome Reveals Its Intracellular Role in the Cytosolic Population - Jessica A. Klein (American Society for Microbiology, 2017)
ABSTRACT The Salmonella invasion-associated type III secretion system (T3SS1) is an essential virulence factor required for entry into nonphagocytic cells and consequent uptake into a Salmonella-containing vacuole (SCV). While Salmonella is typically regarded as a vacuolar pathogen, a subset of bacteria escape from the SCV in epithelial cells and eventually hyperreplicate in the cytosol. T3SS1 is downregulated following bacterial entry into mammalian cells, but cytosolic Salmonella cells are T3SS1 induced, suggesting prolonged or resurgent activity of T3SS1 in this population. In order to investigate the postinternalization contributions of T3SS1 to the Salmonella infectious cycle in epithelial cells, we bypassed its requirement for bacterial entry by tagging the T3SS1-energizing ATPase InvC at the C terminus with peptides that are recognized by bacterial tail-specific proteases. This caused a dramatic increase in InvC turnover which rendered even assembled injectisomes inactive. Bacterial strains conditionally expressing these unstable InvC variants were proficient for invasion but underwent rapid and sustained intracellular inactivation of T3SS1 activity when InvC expression ceased. This allowed us to directly implicate T3SS1 activity in cytosolic colonization and bacterial egress. We subsequently identified two T3SS1-delivered effectors, SopB and SipA, that are required for efficient colonization of the epithelial cell cytosol. Overall, our findings support a multifaceted, postinvasion role for T3SS1 and its effectors in defining the cytosolic population of intracellular Salmonella. IMPORTANCE A needle-like apparatus, the type III secretion system (T3SS) injectisome, is absolutely required for Salmonella enterica to enter epithelial cells; this requirement has hampered the analysis of its postentry contributions. To identify T3SS1-dependent intracellular activities, in this study we overcame this limitation by developing a conditional inactivation in the T3SS whereby T3SS activity is chemically induced during culture in liquid broth, permitting bacterial entry into epithelial cells, but is quickly and perpetually inactivated in the absence of inducer. In this sense, the mutant acts like wild-type bacteria when extracellular and as a T3SS mutant once it enters a host cell. This “conditional” mutant allowed us to directly link activity of this T3SS with nascent vacuole lysis, cytosolic proliferation, and cellular egress, demonstrating that the invasion-associated T3SS also contributes to essential intracellular stages of the S. enterica infectious cycle.